PENYULUHAN TENTANG PENTINGNYA PENDIDIKAN MORAL PADA MASYARAKAT DI DESA TOSANAN, KECAMATAN KAUMAN, KABUPATEN PONOROGO - Nuraini, Ririn; Syafieq Qolby, Muhammad (Institut Agama Islam Riyadlotul Mujahidin, 2024)
Morals are an order in social life that regulates behavior that is permitted or prohibited to be carried out by a person. In reality, the moral education taught in schools has not been fully accepted by children. Therefore, support from family and environment is needed. Especially when someone has been faced with real social life. Moral degradation is still a topic that is increasingly discussed in various levels of society. This research aims to provide education to the public about the importance of moral education in society. The research approach used is a qualitative approach with a case study type of research. Data was collected through interviews, observation and documentation. The data analysis uses the Miles and Huberman interactive model. The results of the research show that the implementation of outreach about the importance of community moral education in Tosanan village, Kauman sub-district, Ponorogo regency went through several stages: Initial preparation, Opening, Delivery of outreach material, Discussion, Evaluation, Closing and Follow-up. The implications of counseling about the importance of moral education in society have a positive impact. This is proven by an increase in public understanding of moral education. People's behavior is more organized than before and noble morals are always prioritized in everyday life.